This Much Water: A qualitative study using behavioural theory to develop a community service video to prevent child drowning in Western Australia - Denehy, Mel; Leavy, Justine; Jancey, Jonine; Nimmo, L.; Crawford, Gemma (BMJ Group, 2017)
Objectives Drowning in children under the age of 5 is a frequently occurring, yet preventable event. This research used behavioural theory to test the suitability and appropriateness of a drowning prevention message in a community service video. Design This qualitative study used content analysis of focus groups. Constructs from the Health Belief Model guided the data analysis. Setting Community organisations and playgrounds in Perth, Western Australia. Participants Participants were parents or carers of at least one child under 5 years residing in Western Australia. Seven focus groups (n=57) were conducted with eight participants in each group. Most participants were parents (96%), female (95%), aged between 25 and 34 years (63%) and were born in Australia (68%). Results Participants indicated the community service video was credible in communicating the message that young children were susceptible to drowning in shallow water and that various water hazards existed in and around the home. However, a range of external factors, such as the child's age, type of water hazard, presence of siblings and other environmental factors, influenced risk perceptions. Child drowning was seen as a serious issue. Controlling access to water and the role of supervision were understood to be important factors in preventing drowning. Conclusions The lack of published drowning prevention interventions shaped by behavioural theory limits the understanding of best practice. Using constructs from the Health Belief Model, this research confirmed the perceived seriousness, devastating and unforgettable consequence of drowning; however, findings were mixed regarding cues to action. Future development of drowning prevention media messages should test strategies to increase susceptibility and self-efficacy among the target group and explore the impact of different message senders. The findings provide a valuable understanding of possible messages and their execution for use in media campaigns, as one component of an effective public health intervention to prevent child drowning underpinned by behavioural theory. © 2017 Article author(s) (or their employer(s) unless otherwise stated in the text of the article).